A Single-Center Pilot Study of Therapeutic Apheresis in Patients with Severe Post-COVID Syndrome - Korth, Johannes; Steenblock, Charlotte; Walther, Romy; Barbir, Mahmoud; Husung, Michael; Velthof, Ansgar (Hormone and Metabolic Research, 2024)
After the COVID-19 pandemic, many patients have reported chronic fatigue and severe post-exertional malaise, with symptoms similar to those of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). The accumulation of agonistic receptor autoantibodies targeting beta-adrenergic (β1 and β2) and muscarinic (M3 and M4) neurotransmitter receptors may play a crucial role in the pathomechanism of both ME/CFS and post-COVID conditions. Therapeutic apheresis has been suggested as an effective treatment option for alleviating and mitigating symptoms in this desperate group of patients. In this single-center pilot study, we analyzed autoantibodies in a cohort of 20 post-COVID patients before and after therapeutic apheresis. Apheresis resulted in a decline of β1 or β2 adrenergic receptor antibodies in all patients. Additionally, the majority of patients experienced a concurrent reduction in symptoms such as fatigue, physical activity restrictions, myalgia, post-exertional malaise, and concentration disorders. This study clearly demonstrates an association between autoantibodies and the clinical improvement of post-COVID patients. Even if future sham-controlled trials do not show a positive outcome, extracorporeal apheresis may still be valuable for this patient group by temporarily improving microperfusion and symptoms. Success in restoring patients to work and normal life, as observed in many individuals after therapeutic apheresis, should be recognized. Therefore, we believe that extracorporeal therapeutic apheresis, as part of a multimodal treatment, should be considered an early intervention for postinfectious syndromes in selected patients.
Keywords: apheresis; long-COVID; post-COVID; chronic fatigue; neurotransmitter; immunity; autoantibodies